A comparative study of the resources, services and clientele of selected education libraries in Metro Manila with implication for the establishment of a national education information network - Mohamed, Awadiah S. (1987)
The study aims to describe the resources and to identify types of users and services provided by libraries in Metro Manila serving graduate teacher education programs. The study also aims to describe the status and prospects of resource sharing among the libraries. It was designed and carried out in August and September 1986. Six teacher education college libraries, 15 university main libraries, 3 college/institute libraries, 3 special libraries and The National Library comprise the sample of the study.